2013
DOI: 10.1016/j.otsr.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Total elbow arthroplasty for acute distal humeral fractures in patients over 65 years old – Results of a multicenter study in 87 patients

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 23 publications
1
51
0
2
Order By: Relevance
“…The multicentric study of Mansat et al [11] (n=87) showed that primary TEA after distal humerus fractures provides satisfactory functional results as well as a painless and stable elbow. After a follow-up of 37.5 months a mean extension-flexion of 97°±22°with 48 % above 100°w as reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multicentric study of Mansat et al [11] (n=87) showed that primary TEA after distal humerus fractures provides satisfactory functional results as well as a painless and stable elbow. After a follow-up of 37.5 months a mean extension-flexion of 97°±22°with 48 % above 100°w as reached.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the elderly a low-density bone structure is expected with an increasing risk of osteosynthesis failure [10]. Total elbow arthroplasty (TEA) is an alternative treatment, which provides immediate satisfactory results with pain relief, a stable and functional elbow and a low complication rate [11,12]. However the postoperative weight-bearing is lifelong limited to a maximum of 5 kg and the survival rate is critically discussed [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of distal humeral fracture treatment is anatomic reconstruction with preservation of the elbow joint. Total elbow arthroplasty represents an alternative treatment option providing immediate pain relief with a stable and functional elbow [6,7]. The functional results after TEA are mostly good to excellent [6,[8][9][10][11][12][13][14][15][16], but weight-bearing is limited to a maximum of 5 kg lifelong, and the longterm implant survival is as yet unknown [17].…”
Section: Introductionmentioning
confidence: 99%
“…Total elbow arthroplasty (TEA) has been indicated for numerous degenerative inflammatory and traumatic elbow diseases [1][2][3][4]. Semiconstrained designs are usually used, allowing a certain degree of valgus/varus of the ulnar component in the hinge mechanism.…”
Section: Introductionmentioning
confidence: 99%